INTERPERSONAL COMMUNICATION RELATIONSHIPS AND LIBRARIES: A SYSTEMATIC LITERATURE REVIEW - Mustofa, Muhamad Bisri; Fegi Sentiana; Faizafati Matus Zahro; Siti Wuryan (Universitas Islam Negeri Mataram, 2023)
This study uses the Systematic Literature Review (SLR) method to explore the relationship between interpersonal communication and libraries, focusing on the role of librarian-user interactions in fostering a comfortable atmosphere and ensuring user satisfaction. Our research shows a positive correlation between effective interpersonal communication and success in the library environment. Our findings underscore the importance of librarians' direct involvement in achieving a high quality library through good interpersonal communication, thereby increasing user satisfaction. This research contributes valuable insights to understanding the dynamics of interpersonal communication within libraries, paving the way to improve communication strategies and enhance user experience.